Detection of soluble urokinase type plasminogen activator receptors in children with gingivitis and normal subjects - Mohamed Abd‑Ellatif El‑Patal; Mona A. Khalil; Walaa Shipl; Ibrahim Barakat; Eman M. I. Youssef; Shahinaz El Attar; Adel Fathi; Alaa A. Abdallah (BMC Oral Health, 2022)
Abstract Background Gingivitis is a reversible condition; however, if left untreated, it progresses to periodontitis, which a serious infection that leads to bone destruction. Soluble urokinase-type plasminogen activator receptor (suPAR) measurement may be of value in the early assessment of gingivitis in children, thereby minimizing risk of tooth loss. Objectives In this observational study, we assessed salivary and serum concentrations of suPAR for the diagnosis of gingivitis and correlation of salivary suPAR with the periodontal clinical parameters. Methods Ninety children participated in the study, with 20 healthy subjects as controls and 70 patients with gingivitis. The gingivitis group was divided into mild, moderate, and severe cases. According to the gingival index (GI), salivary and serum samples were analyzed for the suPAR and C-reactive protein levels using an enzyme-linked immunosorbent assay. Results The salivary suPAR was significantly higher in patients with gingivitis (10.8 ± 2.9 ng/mL) than in the control group (7.0 ± 1.1 ng/mL) as P < 0.001. SuPAR was correlated with gingivitis severity. It was 7.7 ± 1.5 1 ng/mL in mild cases, 10.9 ± 1.2 ng/mL in moderate cases, and 14.4 ± 0.9 ng/mL in severe cases. The difference was significantly high (P < 0.001) between the groups; however, the difference between the mild cases and the control was nonsignificant as P < 0.066. The salivary suPAR was correlated with periodontal clinical parameters, which included GI and simple oral hygiene index (SOHI). Conversely the serum suPAR was not correlated with the salivary suPAR or the periodontal clinical parameters. Conclusion The results of the present study demonstrated that the salivary suPAR is increased in proportionate with the degree of severity of gingivitis in children. Moreover, salivary suPAR was correlated with the periodontal clinical parameters.